Belize. Annual report 2004 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2019)
Presents the results of IICA's management in compliance with the activities proposed in the National Agenda. It addresses the issues of competitiveness and global trade, promotion of food security and agricultural health, strengthening of rural communities, hemispheric integration, development of human capital, environmental management, and institutional modernization